Gamifikasi Sistem Kerja dan Siasat Pengemudi Gojek - Devita Aditya Wicaksono (Calathu: Jurnal Ilmu Komunikasi, 2020)
This study aims to identify how gamification is in the work system of Gojek and how its drivers handle it. This study was conducted through observations and interviews with Gojek drivers operating in Yogyakarta. Based on the concept of sharing economy and gamification, this study revealed that the gamification work system blurs the boundaries between working and playing. A driver's job is not just taking passengers, delivering goods or food. However, it is like playing a "game". The driver has to calculate the mission, target points, bonus, and performance to earn income. The driver is also feared of termination of business partnership termination if he/she violates the applicable rules. This gamification system is closely related to the "partnership" between the driver and the Gojek company. Instead of having an equal relationship, this relationship creates the illusion of freedom and gamification of the work system and the lure of a bonus. Thus, this gap can be exploited by Gojek.